Nugget Processing with Addition of Egg Shell Flour in Kotabaru Village, Jambi - Suryono, Suryono; Perdana, Silvia Mawarti; Nizori, Addion (Abdi Masyarakat, 2024)
Calcium is an essential micronutrient for children to the postmenopausal women. In practice, consumption of calcium-rich foods sourced from animal protein foods for family members, especially children, is still low. Egg shells contain calcium which can be fortified into nuggets to produce calcium-rich nuggets. Thus, the high benefits of egg shells will be obtained and reduce the negative environmental waste impact. Kota Baru Village, Geragai Subdistrict, Tanjung Jabung Timur Regency was chosen as the location for community service because apart from being an UNJA’s integrated laboratory village, this area is one of the location for stunting reduction in Jambi Province. This community service project has target of producing nugget products with the addition of egg shell flour, as well as increasing the knowledge and skills of village business group members. Evaluation of participants' knowledge and skills was carried out using pre-test and post-test questionnaire and checklist of nugget-making procedures. The results of this community service showed that there was a difference in 10 participants' knowledge compared to before the training (test score from 72 to 88). The hedonic test showed that more participants really liked the eggshell and carrot nuggets formulation in terms of smell, texture, and taste. Processing of nuggets with the addition of eggshell flour can be an alternative local food source of animal protein which is also of economic value.